2018
DOI: 10.18805/ijar.b-3339
|View full text |Cite
|
Sign up to set email alerts
|

Gross efficiency of protein and metabolisable energy utilization of sugarcane press residue incorporated in layer diets

Abstract: Sugarcane press residue (SPR), a nonconventional feed ingredient is a soft, spongy, amorphous, dark brown to white material was fed to 32-week-old white-leghorn-layer at 0, 5, 10 and 15 per cent either in the soya-based or fish-based diets to form T1 to T8 diets, respectively. Each diet so formulated was offered to five-replicates of four laying-hens each constituting a total of one-sixty birds reared for 84-days. Results revealed that the cumulative efficiency of protein utilization values of layers fed diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…A byproduct of the sugar industry, sugarcane filter cake is also known as sugarcane mud, sugarcane press residue, or filter press cake [59]. It is an unconventional feed item that ranges in color from dark brown to white and is soft, spongy, and amorphous [33]. One of the byproducts of the 30 million tons of SFC produced annually worldwide, it comes from commercial sugarcane factories.…”
Section: Sugar Cane Filter Cakementioning
confidence: 99%
See 1 more Smart Citation
“…A byproduct of the sugar industry, sugarcane filter cake is also known as sugarcane mud, sugarcane press residue, or filter press cake [59]. It is an unconventional feed item that ranges in color from dark brown to white and is soft, spongy, and amorphous [33]. One of the byproducts of the 30 million tons of SFC produced annually worldwide, it comes from commercial sugarcane factories.…”
Section: Sugar Cane Filter Cakementioning
confidence: 99%
“…However, because SPR has a higher level of lipids, lipase and lecithin added to meals may improve the hydrolysis and emulsification of SPR's lipids and enhance the effects of in situ lipase and lecithin. In addition to inorganic matter, Sumaya et al [33] reported that SFC can be added up to 15% to broiler and layer diets based on fish and soy for the purpose of utilizing protein and energy. According to Dhas [62], broiler growth performances, feed intake, and egg shell and yolk quality were all enhanced by up to 15% SFC in chicken rations.…”
Section: Sugar Cane Filter Cakementioning
confidence: 99%